Assessment of groundwater quality with special reference to arsenic in Nawalparasi district, Nepal using multivariate statistical techniques - Yadav I.C.; Devi N.L.; Mohan D.; Shihua Q.; Singh S. (My University, 2025)
Groundwater is a precious resource for humankind not only in Nepal but also across the globe due to its diverse functions. A total of 48 groundwater samples were collected from three villages of Nawalparasi district, Nepal, during pre-monsoon and monsoon to estimate the overall groundwater quality and to identify the sources of contamination with emphasis on arsenic (As). The average concentrations of all tested groundwater quality parameters (temp., pH, EC, ORP, Ca2+, Mg2+, Na+, K+, Cl-, F-,SO4 2-, PO4 3-, HCO3 -, NO3 -, Cu, Ni, Mn, Cd, Pb, Fe, Zn, Cr, and As) were well within permissible limits of WHO for drinking water, except for Ni, Cd, Pb, Cr, and As. Concentration of As ranged from 60 to 3,100 μg L-1 and 155 to 1,338 μg L-1 in pre-monsoon and monsoon, respectively. The Piper diagram of the groundwater chemistry showed groundwater of Nawalparasi belongs to Ca-Mg-HCO3 and Mg-HCO3 water type with HCO3 - as dominant ions. As content in the study area was negatively correlated with Fe in pre-monsoon, while it was positively correlated in monsoon. Furthermore, As was negatively correlated with oxidation reduction potential suggesting reducing condition of groundwater. Principal component analysis revealed seven major factors that explained 81.996 and 83.763 % of total variance in water quality in pre-monsoon and monsoon, respectively. The variance of water quality was related mainly with the degree of water-rock interaction, mineralization, and anthropogenic inputs. © 2013 Springer-Verlag Berlin Heidelberg.